ANALISIS FRAMING MODEL ZHONDANG PAN DAN M. KOSICKI MENGENAI PEMBERITAAN GANJAR PRANOWO YANG TAMPIL DALAM TAYANGAN AZAN DI TV SWASTA: PADA MEDIA MASSA ONLINE INEWS.ID DAN METROTVNEWS.COM (PERIODE 11-19 SEPTEMBER 2023) - Marfu'ah, Isgiyanti; Riyanto, Buddy; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The function of the media is to influence. One example is how the media is used as a tool to conduct political campaigns with the aim of providing impression management. As in the azan broadcast featuring presidential candidate Ganjar, election observers argue that this is identity politicization. A journalist is inseparable from their perspective in analyzing the data they get in the field. With the different perspectives of journalists in observing facts, the term framing emerged. iNews.id and Metrotvnews.com have different views on the appearance of Ganjar in the azan broadcast on private TV. The purpose of this research is to find out how iNews.id and Metrotvnews.com media framed the case of Ganjar's appearance on the azan broadcast. Using Zhondang Pan and Kosicki's framing analysis theory to determine the reality created by revealing script, syntax, thematic, and rhetorical elements. The results showed that iNews.id and Metrotvnews.com carried out media framing by selecting headlines, sources, source quotes and image placement which were used as tools to frame the news of the two media. by selecting headlines, sources, source quotes and image placement which were used as tools to frame the news of the two media. From the results of this research, it can be concluded that iNews.id media made a pro framing of Ganjar while Metrotvnews.com media framed Ganjar with disapproval/contra.